2009
DOI: 10.1136/jech.2008.085738
|View full text |Cite
|
Sign up to set email alerts
|

The association between urban or rural locality and hip fracture in community-based adults: a systematic review

Abstract: Urban or rural locality has been suggested to influence musculoskeletal health, with lower bone mineral density (BMD) and greater prevalence of fracture identified in urban residents. A computer-aided search of Medline, EMBASE, CINAHL and PsychINFO, January 1966 to November 2007 was conducted to identify studies investigating the relationship between urban or rural locality and the occurrence of hip fracture. The methodological quality of studies was assessed, and a best-evidence synthesis was used to summaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 69 publications
1
37
0
1
Order By: Relevance
“…Our "best-evidence synthesis" was conducted as previously published [16,24] and consisted of five levels of evidence that reflected the study design used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our "best-evidence synthesis" was conducted as previously published [16,24] and consisted of five levels of evidence that reflected the study design used.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the methodological quality of the included studies, two reviewers (SLB and YW) independently scored them using the adapted scoring system of Lievense et al [22,23] as presented in Table 1 and previously applied [16,24]. Each of the 14 items was scored as positive (1), negative (0), or unclear (?…”
Section: Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…These variations could reflect differences in several underlying risk factors, such as ethnicity, body mass index, vitamin D and sun exposure, smoking patterns, physical activity and medication use [1,7,8]. Although the cause of the discrepancy is most likely multifactorial, it is plausible that environmental factors may play a role [6,8].We have previously reported that variations in drinking water quality across Norway, in particular a higher acidity level (lower pH) in urban compared to rural areas, may be related to self-reported fractures of the forearm [9]. The pH level is generally positively correlated with the concentrations of calcium and magnesium in the water.…”
mentioning
confidence: 96%
“…Predictions indicate that hip fracture incidence will increase 6-fold in Africa and Asia by 2050, partially attributed to demographic transition and population ageing (2) . Differences in areal bone mineral density (aBMD) between rural and urban locations indicate that urban regions of high income countries (HIC) have lower aBMD and a higher incidence of hip fracture (3) . The few studies conducted in low and middle income countries (LMIC) provide inconsistent results; in contrast to HIC, most have found higher aBMD in urban populations (4) .…”
mentioning
confidence: 99%